Small is Beautiful: Economics As if People Mattered (an excerpt) - SchumacherErnst Friedrich (Journal of Economic Sociology, 2012)
In his famous book Ernst Schumacher proposes a revolutionary view on the economic structure of the Western world. Schumacher argues that human inclination to progress and profit seeking contributing to formation of gigantic enterprises and increasing specialization actually results in economic inefficiency, environment pollution, and deplorable labour conditions. The author challenges the doctrine of economic, technological and scientific specialization and proposes an idea of «intermediate technology» system based on small working units, new property relations, and utilization of local labour and resources. The journal «Economic Sociology» publishes an excerpt «A Question of Size» in which the author convincingly demonstrates that economics has to deal with the world of people not goods and abstract concepts.